2019
DOI: 10.1177/0954409719826824
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the vibration characteristics of the floating slab track in metro turnout zones

Abstract: In railway turnout areas, vertical and horizontal structure irregularities, including geometry and stiffness, result in vibration amplification during the passage of trains. These vibrations can then spread to the surrounding environment. A steel spring floating slab track may be used to control such vibrations, especially in metro-type urban railways. An experimental study was conducted to investigate the vibration-mitigating effects of the floating slab track in turnout areas, and the results were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The point-supported floating-slab track is designed based on the mass-spring-damping theory, and the purpose of vibration reduction is achieved by reducing the natural frequency of the structure. At present, many studies have evaluated the point-supported floating-slab track (Huang et al, 2018; Jiang et al, 2019; Lei and Jiang, 2016; Lombaert et al, 2006; Nelson, 1996). For example, the research of Cui and Chew (2000) showed that compared with the ordinary track structure, the floating-slab track can effectively attenuate the vibration in the frequency domain of its designed vibration reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The point-supported floating-slab track is designed based on the mass-spring-damping theory, and the purpose of vibration reduction is achieved by reducing the natural frequency of the structure. At present, many studies have evaluated the point-supported floating-slab track (Huang et al, 2018; Jiang et al, 2019; Lei and Jiang, 2016; Lombaert et al, 2006; Nelson, 1996). For example, the research of Cui and Chew (2000) showed that compared with the ordinary track structure, the floating-slab track can effectively attenuate the vibration in the frequency domain of its designed vibration reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have done some research on the identification of track modal parameters using laboratory tests [6], field tests [7]- [10], and numerical analysis [11], [12]. However, they have two common limitations: (1) only track modal parameters of a certain state can be obtained; (2) only track modal parameters of a certain section can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, many different theoretical models are available to simulate the dynamic behavior of railway tracks, which plays an important role on the generation of vibration and rolling noise [3][4][5]. In these models, Hertz wheel/rail contact model was common used and irregularities between wheel-rail were considered as the excitation element.…”
Section: Introductionmentioning
confidence: 99%